Retinoic Acid: A New Old Friend of IL-17A in the Immune Pathogeny of Liver Fibrosis - Kartasheva-Ebertz, Daria M.; Pol, Stanislas; Lagaye, Sylvie (Frontiers in Immunology, 2021)
Despite all the medical advances mortality due to cirrhosis and hepatocellular carcinoma, the end stages of fibrosis, continuously increases. Recent data suggest that liver fibrosis is guided by type 3 inflammation with IL-17A at the top of the line. The storage of vitamin A and its active metabolites, as well as genetics, can influence the development and progression of liver fibrosis and inflammation. Retinoic acid (active metabolite of vitamin A) is able to regulate the differentiation of IL17A+-producing cells as well as the expression of profibrotic markers. IL-17A and its pro-fibrotic role in the liver is the most studied, while the interaction and communication between IL-17A and vitamin A active metabolites has not been investigated. We aim to update what is known about IL-17 and retinoic acid in the pathobiology of liver diseases.